2019
DOI: 10.1097/md.0000000000016510
|View full text |Cite
|
Sign up to set email alerts
|

Platelet distribution width, platelet count, and plateletcrit in diabetic retinopathy

Abstract: Background: Screening and diagnosis of diabetic retinopathy (DR) mainly depends on fundus examination, which is not an intuitive and simple screening or diagnostic method. Recently, the relationship between platelet parameters and DR has become a hot topic. Whether platelet parameters have clinical value in DR is controversial. Methods: Literature was retrieved by formal search of electronic databases (PubMed, Embase, Cochrane library, Scopus, and CNKI) and by hand sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…A similar conclusion has been found in another type of diabetic microangiopathy; namely, diabetic retinopathy. In a meta-analysis involving 4,653 participants, Ji et al 16 found an obvious decrease of the PLT level in diabetic retinopathy patients. Peripheral PLT depends on several different variables; that is, platelet production rate, mean platelet survival and the size of the exchangeable splenic platelet pool.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar conclusion has been found in another type of diabetic microangiopathy; namely, diabetic retinopathy. In a meta-analysis involving 4,653 participants, Ji et al 16 found an obvious decrease of the PLT level in diabetic retinopathy patients. Peripheral PLT depends on several different variables; that is, platelet production rate, mean platelet survival and the size of the exchangeable splenic platelet pool.…”
Section: Discussionmentioning
confidence: 99%
“…A similar conclusion has been found in another type of diabetic microangiopathy; namely, diabetic retinopathy. In a meta‐analysis involving 4,653 participants, Ji et al 16 . found an obvious decrease of the PLT level in diabetic retinopathy patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both higher lymphocyte and lower platelet counts contribute to higher LPR. Platelets are known to have some physiological characteristics such as adhesion and aggregation [ 31 ]. The increased activation and aggregation of platelets are important causes of vascular complications in diabetes [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increased activation and aggregation of platelets are important causes of vascular complications in diabetes [ 32 ]. In a recent meta-analysis, the authors conjectured that the consumption of platelets during coagulation attributes mainly to the decreased platelets in DR patients [ 31 ]. However, according to our findings, structural and functional outcomes of IVB therapy in DME patients were not in association with platelets’ counts.…”
Section: Discussionmentioning
confidence: 99%